Multi-messenger probes of asteroid mass primordial black holes: Superradiance spectroscopy, Hawking radiation, and microlensing - James B. Dent; Bhaskar Dutta; Tao Xu (Physics Letters B)
Superradiance provides a unique opportunity for investigating dark sectors as well as primordial black holes, which themselves are candidates for dark matter over a wide mass range. Using axion-like particles as an example, we show that line signals emerging from a superradiated axion cloud combined with black hole Hawking radiation in extragalactic and galactic halos, along with microlensing observations lead to complementary constraints on parameter space combinations including the axion-photon coupling, axion mass, black hole mass, and its dark matter fraction, fPBH. For the asteroid mass range ∼1016−1022g, where primordial black holes can provide the totality of dark matter, we demonstrate that ongoing and upcoming observations such as SXI, JWST, and AMEGO-X will be sensitive to possible line and continuum signals, respectively, providing probes of previously inaccessible regions of fPBH parameter space. Further complementarity from a stochastic gravitational-wave background emerging from the black hole formation mechanism is also considered.